2022
DOI: 10.1111/jcpt.13761
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use during the first 6 months of COVID ‐19 pandemic in Iran: A large‐scale multi‐centre study

Abstract: What is known and objective Although antibiotics are ineffective against viral infections, epidemiological studies have revealed that the COVID‐19 pandemic resulted in the overuse of antibiotics and disruption of antimicrobial stewardship programmes. We investigated the pattern of antibiotic use during the first 6 months of the COVID‐19 pandemic in Iran. Methods A multi‐centre retrospective study was designed to investigate the use of 16 broad‐spectrum antibiotics in 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In the present study, we found a high overall rate of antibiotic intake, with more than half of the patients receiving some sort of antibiotic treatment during their hospital stay, and an average of 53.29 DOT/100 patient days. In a multicenter study conducted in Iran, Salehi et al found an average use of 121.6 DDD/100 hospital bed days during the first six months of the pandemic [10]. Interestingly, 74% of patients in the meta-analysis by Chedid et al received some sort of antibiotic therapy during the first wave of the pandemic [11], a rate similar to the figure of 77.6% of patients under an antibiotic treatment during the first wave in our cohort.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, we found a high overall rate of antibiotic intake, with more than half of the patients receiving some sort of antibiotic treatment during their hospital stay, and an average of 53.29 DOT/100 patient days. In a multicenter study conducted in Iran, Salehi et al found an average use of 121.6 DDD/100 hospital bed days during the first six months of the pandemic [10]. Interestingly, 74% of patients in the meta-analysis by Chedid et al received some sort of antibiotic therapy during the first wave of the pandemic [11], a rate similar to the figure of 77.6% of patients under an antibiotic treatment during the first wave in our cohort.…”
Section: Discussionsupporting
confidence: 85%
“…It results from the association of molecules such as interleukins, interferons, chemokines, and TNF-α in patients with COVID-19. A significant elevation of inflammatory markers were observed in patients who received antibiotics, which Have been pointed out as a possible aggravation of the cytokine storm caused by COVID-19 [16,21,22]. Bacteria are able to successfully cause secondary infections in COVID-19 by their virulence factors, such as membrane proteins, secretory systems, adhesins, and glycoconjugates.…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19 pandemic in Iran, it was estimated that each patient received 1.21 DDDs of antibiotics every day ( 20 ). Our study highlighted the need for judicious use of antibiotics in the management of COVID-19 by strengthening antimicrobial surveillance programs.…”
Section: Discussionmentioning
confidence: 99%